KEPUASAN KONSUMEN ATAS KUALITAS PELAYANAN RUMAH MAKAN GRIYA DAHAR MBOK SUM (Studi kasus pada konsumen Daerah Istimewa Yogyakarta) - Nur Rohman, Muhammad Latif; Suji’ah, Uju (Journal Competency of Business, 2021)
This study aims to determine the effect of service quality (tangible/X1, reability/X2, responsiveness/X3, assurance/X4, and emphaty/X5) on customer satisfaction. Data collection was carried out by distributing questionnaires to 100 consumers who had bought at the Griya Dahar Mbok Sum restaurant who were domiciled in the Special Region of Yogyakarta. The sampling technique used was purposive sampling technique. The analytical method used is multiple linear regression, simultaneous significance test (F test), partial significance test (t test), and coefficient of determination test (R2 test). The study found that service quality (tangible/X1, reability/X2, responsiveness/X3, assurance/X4, and emphaty/X5) partially (t-test) had a significant effect on customer satisfaction, while service quality (tangible/X1, reability/X2, responsiveness/X3, assurance/X4, and emphaty/X5) simultaneously (F test) have a significant effect on customer satisfaction. The results of the coefficient of determination (R2) show the effect of service quality (tangible/X1, reability/X2, responsiveness/X3, assurance/X4, and emphaty/X5) on customer satisfaction of 81.5%, while the remaining 18.5% is influenced by other factors not studied. The coefficient of the variable that has the most influence on consumer satisfaction is the reliability variable/X2 of 3.787.